The Type of Per-Cooling Strategies Currently Employed by Competitive and Professional Cyclists-Triathletes During Training and Competition Are Condition (Dry vs. Humid) Dependant - Bayne, Freya; Racinais, Sebastien; Mileva, Katya N.; Hunter, Steve; Gaoua, Nadia (Frontiers in Sports and Active Living, 2022)
Purpose To investigate cooling strategies employed by athletes (cyclists-triathletes) during training and competition in hot and dry (HD) and hot and humid (HH) conditions. Methods Thirty-five athletes completed an online questionnaire on the type, timing, and justification of cooling strategies employed during past training and/or competitions in HD and HH conditions. In addition, 3 athletes also completed a one-to-one follow-up interview. Results Comparisons between strategies employed in all conditions were based on N = 14 (40%). Cold-water pouring was the most employed (N = 4; 21%) strategy during training and/or competing in hot conditions. The timing of the strategies employed was based on pitstops only (N = 7; 50%). The justification for strategies employed was based on trial and error (N = 9, 42.85%: N = 10, 47.61%). All athletes rated strategies employed as 1 (“not effective for minimising performance impairments and heat-related illnesses”). Comparisons between HD and HH were based on N = 21 (60%), who employed different strategies based on condition. Cold-water ingestion was the most employed (N = 9, 43%) strategy in HD, whereas a combination of cold-water ingestion and pouring was the most employed (N = 9, 43%) strategy in HH. The timing of strategies employed in the HD split was pre-planned by distance but was modified based on how athletes felt during (N = 8, 38%), and pre-planned by distance and pit stops (N = 8, 38%). The timing of strategies employed in HH was pre-planned based on distance and how athletes felt during (N = 9, 42%). About 57% (N = 12) of the 60% (N = 21) perceived effectiveness in HD and HH as 3 (“Sometimes effective and sometimes not effective”), whereas 43% (N = 9) of the 60% (N = 21) perceived effectiveness in HD and HH as 4 (“Effective for minimising performance impairments”). Conclusion Cold-water ingestion is the preferred strategy by athletes in HD compared to a combination of cold-water ingestion and pouring in HH conditions. All strategies were pre-planned and trialled based on distance and how athletes felt during training and/or competition. These strategies were perceived as effective for minimising performance impairments, but not heat-related illnesses. Future studies should evaluate the effectiveness of these cooling strategies on performance and thermoregulatory responses in HD and HH conditions.